Computational study of wind flow and pollutant dispersion near tree canopies - Salim, Salim Mohamed (2011)
Air quality in urban and industrial complexes is of great importance owing to the many implications on human and environmental health. Air pollution in built-up areas is typically associated with traffic exhaust emissions. High pedestrian level concentrations are the result of a non trivial combination of pollutant sources, climate and city morphological configurations. The increase of urbanisation puts a strain on city resources, resulting in increased use of transport and a denser and more compact urban fabric. The consequence of such a change in city morphology exacerbates current human air pollution exposure. There have been several Computational Fluid Dynamics (CFD) studies on air pollution problems in urban areas, which have largely centred on employing the conventional Reynolds-Averaged Navier-Stokes (RANS) approach, and in all of these investigations, the RANS models have been reported to numerically overpredict pollutant concentration levels when compared to wind tunnel (WT) measurements. In addition, the majority of previous investigations have failed to account for the aerodynamic effects of trees, which can occupy a significant portion of typical urban street canyons. The presence of trees aggravates the pollutant concentration at pedestrian level by altering the air circulation and ventilation. Trees act as obstacles to the airflow, reducing wind velocity within street canyons and restricting air exchange with the above-roof flow. As a result fewer pollutants are dispersed out of the canyon. To address shortcomings of previous numerical investigations, the work undertaken in this project has two main objectives. The study first aims to implement Large Eddy Simulation (LES) to improve the flow and concentration predictions, and second to demonstrate the aerodynamic impacts of trees. A wall y+ approach is used to determine the computational grid configuration and corresponding RANS turbulence model. The approach is evaluated in the present numerical study and is found to be exceptionally useful in resolving flow structures near shear zones, particularly in tree-lined canyons. This allows for the appropriate mesh resolution to be selected, when taking into account a compromise between prediction accuracy and computational cost. In part one of the project, the prediction accuracy of the pollutant dispersion within tree-free urban street canyons of width to height ratios W/H = 1 and W/H=2, are examined using two steady-state RANS turbulence closure models - the standard k-ε and Reynolds Stress Model (RSM) and LES coupled with the advection-diffusion method for species transport. The numerical results, which include the statistical properties of pollutant dispersion, e.g. the mean concentration distributions, the time-evolution and three-dimensional spreads of the pollutant, are then compared to WT measurements available from the online database (CODASC, 2008) www.codasc.de. The accuracy and computational cost of both numerical approaches are compared. The time-evolution of the pollutant concentration (for LES only) and the mean values are presented. It is observed that amongst the two RANS models, RSM performs better than standard k-ε except at the centreline of the canyon walls. However, LES, although more computationally expensive, does better than RANS. A supplementary investigation is performed to illustrate that unsteady RANS (URANS) is not a suitable replacement for LES when wishing to resolve the internally induced fluctuations of flow and concentration fields. URANS fails to capture the transient mixing process. Part two of the research extends the study from the tree-free street canyons by investigating the aerodynamic influence of tree plantings. Configurations of W/H=1 with single row of trees and W/H=2 with two rows of trees are simulated. In both cases, two tree crown porosities are studied, one for a loosely (Pvol = 97.5%) and another for a densely (Pvol = 96%) packed tree crown, corresponding to pressure loss coefficients λ = 80 m-1 and λ = 200 m-1, respectively. Results of the tree-lined cases are then compared to the tree-free street canyons from the previous investigation. It is observed that the presence of trees reduces the in-canyon circulation and air exchange, thus increasing the overall concentration levels. Similar to the tree-free cases, LES performs better than RANS. In addition, it is shown that a wider street W/H = 2 with two rows of trees promotes better air ventilation and circulation with lower pollutant accumulation at pedestrian level, as opposed to a narrow street W/H = 1 with one row of trees. This is also true for tree-free cases.